POTENTIAL FISHING GROUND MAPPING BASED ON GIS HOTSPOT MODEL AND TIME SERIES ANALYSIS: A CASE STUDY ON LIFT NET FISHERIES IN SERIBU ISLAND - Andi Alamsyah Rivai; Vincentius P. Siregar; Syamsul B. Agus; Hiroki Yasuma (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Information on the spatial and temporal of fishing activity can optimize a fisheries management and increase their economical and biological benefit. For effective management and good understanding of fishing activities, information about fishing ground is crucial. In this study, we aimed to analyze the spatio-temporal of lift net fisheries in Kepulauan Seribu by analyzing their fishing season, investigating their hotspot of fishing ground using GIS-based hotspot model, and mapping the potential fishing ground of each target species. We found that anchovy and scad could be caught throughtout the year, while sardine and squid had high fishing season in west monsoon. Hotspot of fishing ground of lift net fisheries in Kepulauan Seribu waters generally was concentrated around Lancang Island and in southern part of Kotok Island. Potential fishing ground for sardines was located in around Lancang Island on west monsoon. Squids were highly distributed around Lancang Island in December to January and around Lancang and Rambut Islands in November. Anchovy and scad had more potential fishing ground in around Kepulauan Seribu waters.  Keywords: fishing ground, lift net, hotspot, fishing season